2001
DOI: 10.5507/bp.2001.011
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Rat Cardiomyocytes - A Model for the Study of Morphological, Biochemical and Electrophysiological Characteristics of the Heart

Abstract: The neonatal rat cardiomyocyte model enables heart researchers to study and understand the morphological, biochemical and electrophysiological characteristics of the heart. This model offers a broad spectrum of experiments, such as studies of contraction, ischaemia, hypoxia and the toxicity of various compounds. This review examines the methodology for the isolation and cultivation of primary neonatal rat cardiomyocyte cultures, considers possible problems and pitfalls, and presents an optimized protocol for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 67 publications
(183 reference statements)
2
80
0
1
Order By: Relevance
“…Furthermore, studies have demonstrated that cultured neonatal cardiomyocytes form functional electromechanical coupling more comparable with an in situ heart (48). Adult rat cardiomyocytes are particularly sensitive to culture conditions; they lack resistance to cellular disintegration and quickly lose their contraction capability (6).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have demonstrated that cultured neonatal cardiomyocytes form functional electromechanical coupling more comparable with an in situ heart (48). Adult rat cardiomyocytes are particularly sensitive to culture conditions; they lack resistance to cellular disintegration and quickly lose their contraction capability (6).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyocytes were centrifuged, washed, and then preplated (3 times, 1 h each to remove nonmuscle cells and cell debris) in growth medium (see below). The isolation procedure has been previously described (11). Untransfected neonatal mouse cardiomyocytes showed spontaneous beating within 2 days after the isolation procedure, and this could be observed for up to 10 days of cell culture.…”
Section: Methodsmentioning
confidence: 99%
“…17 More than 90% of cells were cardiomyocytes (positive for ␣-actinin). Adenovirus-mediated transfection efficiency in cardiomyocytes is 90% to 95%.…”
Section: Rat Neonatal Cardiomyocytesmentioning
confidence: 99%